Cerebrovascular accidents in patients with type 2 diabetes mellitus - Sergey Valentinovich Kakorin; E V Tulyakova; K V Voronkova; Ashot Musaelovich Mkrtumyan (Сахарный диабет)
Cerebrovascular accident (CA) is a nowadays widely spread, highly incapacitating and often lethal event that poses a prominent clini- cal problem. Cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM) ? an ?epidemic? of the century, ? are known to be its primary risk factors. Hyperglycemia promotes CA risks by induction of protein glycosylation, elevation of blood plasma atherogenic potential, activation of coagulation system with higher risk for thrombosis and disturbance of microcirculation on tissue and organ lev- els. Influence of hyperglycemia on severity and extent of neurologic damage is still under evaluation. Development of macroangiopathy is thought to be associated with media calcification, distal polyneuropathy and renal disorders, all of which are cardiovascular risk factors. Application of so-called metabolic drugs resulted in certain disillusionment, as these agents failed to prove their efficacy during clinical trials. Incidence of pulmonary edema in patients with ischemic CA and T2DM is important as it dictates the necessity for use of loop diuretics. Incidence and severity of heart failure and its correlation with degree of glycemic disorders, incidence of pulmonary em- bolism, as well as tactics of management and prognosis in patients with ischemic CA and T2DM, remains a relevant research problem.